Acinar Cell Carcinoma of the Pancreas: Cytologic, Immunohistochemical, and Ultrastructural Features. Issue 4 (July 2015) - Simmons, Stephanie; Eltoum, Isam A.
Abstract : Abstract: Acinar carcinoma is extremely rare. In this report, we present the clinical and pathologic features of three cases that we have encountered in a busy EUS-FNA service. All 3 cases were diagnosed on final histology using immunostains and electron microscopy. Our cases demonstrated the rarity of this neoplasm and the need for ancillary testing for accurate diagnosis.